ENGINEERING GRAPHICS ADVANCES AND IMPROVEMENTS, NEW PROPOSALS - Jumanazarova Zuhra Qosimjonovna (Research Focus International Scientific Journal, 2025)
The study of graphic communication methods that engineers, architects and designers use to express ideas and concepts, or the graphic expression used in the design process, is becoming increasingly important. Correct interpretation of graphic language allows for the development of skills in the training of an engineer or architect. For this reason, research on this topic is particularly valuable in finding improvements or new proposals that will help to better understand these methods. In this special issue, the reader is presented with examples from the various disciplines available, such as engineering graphics, industrial design, geometric modeling, computer-aided design, descriptive geometry, architectural graphics and computer animation.